The Concept of Pictorial Language in Jean Dubuffet’s Theory and Practice - Blokhina, Ksenia G. (Actual Problems of Theory and History of Art, 2016)
This article analyzes the theory and practice of Jean Dubuffet from the perspective of the linguistic theory. The study is based on the concept of the artistic language described in such articles as “Art Brut is preferable to cultural arts”, 1949 (“L’Art Brut préféré aux arts culturels”), “Anticultural position”, 1951 (“Positions anticulturelles”) and others. Comparing Dubuffet’s judgments with the ideas of structuralism, it is possible to indicate special importance of art in human life. According to the artist, for each individual creative activity is just as organic as language. The artist manifests the language of art as an innate characteristic of each person, free way of thinking, learning, and reflecting the world. This ratio allows Dubuffet to substantiate his understanding of “true” art, and as a consequence, to approve the significance of Art Brut. The comparison of his theoretical work with certain texts by Ferdinand de Saussure and Umberto Eco allows otherwise treat such controversial issues of Brut as unprofessional artists and the interpretation of their works. From a practical point of view, the problem of pictorial language and the material from which it is constructed is considered on a series of examples of paintings devoted to the typical characters of the streets, “Mirobolyus, Macadam & Co” and portraits series.